The grounding argument against non-reductive moral realism - Bader, R (Oxford University Press, 2016)
The supervenience argument against non-reductive moral realism threatens to rule out the existence of irreducibly normative properties by establishing that for every normative property there is a corresponding non-normative property that is necessarily co-extensive with it. This paper first considers but rejects the suggestion that one can address the supervenience argument by insisting that normative properties only supervene with normative but not metaphysical necessity. It then establishes that the standard response to the supervenience argument, which consists in rejecting necessary co-extension as the criterion for property identity, does not suffice for defending non-reductionist views of the normative. In particular, it identifies a hyperintensional analogue of the supervenience argument that threatens non-reductionism even within a hyperintensional setting. This grounding argument against non-reductive moral realism threatens to rule out the existence of irreducibly normative properties by establishing that for every normative property there is a corresponding non-normative property that has the very same grounds and is, accordingly, hyperintensionally equivalent. It is then argued that non-reductionism can nevertheless be salvaged by distinguishing the different grounding relations that are involved in grounding the normative property and the corresponding non-normative property. Nonreductionist versions of moral realism thus turn out to be committed to there being irreducibly different grounding relations.